Sudan : Overview of the Urban Landscape - World Bank (Washington, DC, 2013)
This study responds to the need for information and analysis on the urban sector in Sudan, to inform the Bank's policy dialogue with the Government of Sudan (GoS) on urban and local government issues, and to inform the design of future Bank assistance. The first phase of this analytical exercise, which is the focus of this report, develops an overview of the urban landscape. The report is structured as follows: section two describes the evolution of the spatial system in Sudan and highlights key urbanization patterns and trends; section three provides an overview of the legal, institutional and financial composition of Sudan's urban areas; and section 80 outlines the key policy issues and recommendations. The report also draws on in-depth case studies of Nyala and Khartoum, which are included as annexes to the report.